The Gorontalo Religious Court Judges Response Toward Their Absolute Competence in Resolving Shariah Economy Disputes - Andi Mardiana; Rizal Darwis (Al-Ulum, 2015)
Post the first amendment of Religious Courts Bill that provides wider authority toward Religious Courts in investigate and decide Islamic economics disputes has responses, whether support or pessimistic, especially among Religious Court judges themselves. This paper examines the Gorontalo Religious Courts judges response about their authority in resolve Shariah economy disputes. This paper is a qualitative descriptive research and the data was collected using observation, interviews and document reviews. The finding of this study revealed that the Gorontalo Religious Courts judges response well to trust laws in handling disputes Shariah economy. In other words, in principle, they are ready to handle disputes Islamic economics. Readiness, such as: the handling disputes Shariah economy is Religious Courts judges authorities and it is a professional responsibility as a judge; Religious Courts formed a special judge to handle falling out or cases of Shariah economy, and Religious Courts judges provides knowledge of Shariah economy without trainings or workshops.